Serological and structural characterization of the O-antigens of the unclassified Proteus mirabilis strains TG 83, TG 319, and CCUG 10700 (OA) - Zabłotni, Agnieszka (Birkhäuser-Verlag, 2007)
INTRODUCTION: Lipopolysaccharide (endotoxin, LPS) is an important potential virulence factor of Proteus rods. The serological specificity of the bacteria is defined by the structure of the O-polysaccharide chain (O-antigen) of the LPS. Until now, 76 O-serogroups have been differentiated among Proteus strains. MATERIALS AND METHODS: LPSs were isolated from Proteus mirabilis TG 83, TG 319, and CCUG 10700 (OA) strains by phenol/water extraction. Antisera were raised by immunization of rabbits with heat-killed bacteria. Serological investigations were performed using enzyme immunosorbent assay, passive immunohemolysis, inhibition of both assays, absorption of antisera, and Western blot. RESULTS: The cross-reactive epitope shared by these strains and P. penneri O72a,O72b is located on the O-polysaccharide and is most likely associated with an α-D-Glcp-(1→6)-β-D-GalpNAc disaccharide fragment. The serological data indicated the occurrence of two core types in the LPSs studied, one characteristic for P. mirabilis TG 319 and CCUG 10700 (OA) and the other for P. mirabilis TG 83 and O57. CONCLUSIONS: The serological and structural data showed that P. mirabilis TG 83, TG 319, CCUG 10700 (OA), and O57 have the same O-antigen structure and could be qualified to the Proteus O57 serogroup.